Beliefs and Attitudes Toward Inclusion of Student Teachers and Their Contact With People With Disabilities - Kunz, André; Luder, Reto; Kassis, Wassilis (Frontiers in Education, 2021)
Inclusive schooling has been a key issue in special needs education for the last 20 years. In this context, teacher's attitudes toward inclusion is an essential factor in professional competence. It is therefore in the interest of an inclusive school system that inclusion-related beliefs and attitudes are cultivated in basic teacher education. Although some studies report positive effects of basic teacher education on successful inclusion processes and outcomes at school, the findings on attitude changes in teacher education are inconsistent. Multiple factors influence inclusion-related attitudes and beliefs. Among them, personal contact with people with disabilities is important. The present study at the University of Teacher Education in Zurich, Switzerland, examines the influence of previous contact with people with disabilities on attitudes toward inclusion after initial teacher training modules. An online survey (N = 443) was conducted before (T0) and after (T1) a training module on inclusive education/inclusive teaching. Validated scales on attitudes toward inclusion were used. The findings show that the student teachers report significantly more positive contact with people with disability than negative ones. At the same time, student teachers who are in contact with people with disabilities report a significantly more positive attitude toward inclusion at the beginning of the term, and a higher self-efficacy in dealing with disruptive behavior and interdisciplinary cooperation, as well as an individualizing teaching structure. They also report fewer concerns and negative attitudes than student teachers without such contact. Contact with people with disabilities was significantly related to an anticipated willingness to take on an inclusive class. However, no moderating effect of contact over the term was found. Additionally, we identify a considerable heterogeneity on positive attitudes toward inclusion within the respective groups (i.e., more positive or negative contact) via multigroup latent profile analysis. In particular, higher levels on self-efficacy in dealing with disruptive behavior and individualizing teaching structure were central indicators for positive attitudes toward inclusion; this held for both contact groups.